Archaeological Survey of a Proposed Processing Plant, St. Paul, Robeson County, N.C - Lautzenheiser, Loretta (the Digital Archaeological Record)
This resource is a citation record only, the Center for Digital Antiquity does not have a copy of this document. The information in this record has been migrated into tDAR from the National Archaeological Database Reports Module (NADB-R) and updated. Most NADB-R records consist of a document citation and other metadata but do not have the documents themselves uploaded. If you have a digital copy of the document and would like to have it curated in tDAR, please contact us at comments@tdar.org.